Effects of pulsatile flow on postoperative recovery in adult cardiac surgery with cardiopulmonary bypass: A systematic review and meta-analysis of randomized controlled trials - Weidong Yan; Tianlong Wang; Jing Wang; RuiNing Yang; Han Zhang; Mingru Zhang; Bingyang Ji (Heliyon)
Background: The role of pulsatile versus non-pulsatile flow during cardiopulmonary bypass (CPB) is still in debate. This systematic review aimed to comprehensively assess the impact of pulsatile versus non-pulsatile flow on patients’ recovery. Methods: We searched MEDLINE, EMBASE, and Cochrane Library databases for randomized controlled trials comparing pulsatile and non-pulsatile flow in cardiac surgeries with CPB. Data were analyzed using the random-effects model. Then, sensitive analysis and meta-regression were conducted. Findings: 32 studies including 2568 patients were considered in this meta-analysis. There is no difference in in-hospital mortality between the two groups (risk ratio [RR] = 0.74, 95 % confidence interval [CI] = 0.35–1.56, p = 0.43). The ICU stay for the pulsatile group was still significantly shorter than that for the non-pulsatile group (mean difference [MD] = -0.19, 95%CI = −0.35∼-0.03, p = 0.02). Patients in the pulsatile group experienced a shorted stay in hospital (MD = −0.68, 95%CI = −0.97∼-0.39, p < 0.01) and a lower risk for acute kidney injury (AKI) compared with non-pulsatile group (RR = 0.46, 95%CI 0.35–0.60, p < 0.01). There was no significant difference of the postoperative cognitive dysfunction (POCD) between the two groups no matter the roller pump or the intra-aortic balloon pump was used (RR = 0.98, 95%CI = 0.87–1.11, p = 0.78). Conclusions: The use of pulsatile flow during CPB in heart surgery has a protective effect on patient recovery. It can reduce the incidence of AKI, shorten the ICU and hospital stays, but its positive effect on postoperative mortality and POCD is not yet apparent.